Inverse Estimation of Soil Hydraulic and Transport Parameters of Layered Soils from Water Stable Isotope and Lysimeter Data. Issue 1 (17th May 2018) - Groh, Jannis; Stumpp, Christine; Lücke, Andreas; Pütz, Thomas; Vanderborght, Jan; Vereecken, Harry
Abstract : Core Ideas: To determine the water retention curve from inverse modeling, θ and ψ need to be monitored. δ 18 O ratios contained information to inversely estimate soil hydraulic parameters. Different observation types should be combined in a single OF to estimate parameters. Averages of local measurement could be described using effective parameters. Accurate measurement of fluxes at lysimeter boundaries improved model parameterization. Accurate estimates of soil hydraulic parameters and dispersivities are crucial to simulate water flow and solute transport in terrestrial systems, particularly in the vadose zone. However, parameters obtained from inverse modeling can be ambiguous when identifying multiple parameters simultaneously and when boundary conditions are not well known. Here, we performed an inverse modeling study in which we estimated soil hydraulic parameters and dispersivities of layered soils from soil water content, matric potential, and stable water isotope (δ 18 O) measurements in weighable lysimeter systems. We used different optimization strategies to investigate which observation types are necessary for simultaneously estimating soil hydraulic and solute transport parameters. Combining water content, matric potential, and tracer (e.g., δ 18 O) data in one objective function (OF) was found to be the best strategy for estimating parameters that can simulate all observed water flow and solute transport variables. A sequential optimization, in which first an OF with only water flow variables and subsequently an OF with transport variables was optimized, performed slightly worse indicating that transport variables contained additional information for estimating soil hydraulic parameters. Hydraulic parameters that were obtained from optimizing OFs that used either water contents or matric potential could not predict non‐measured water flow variables. When a bromide (Br − ) tracer experiment was simulated using the optimized parameters, the arrival time of the bromide pulse was underestimated. This suggested that Br − sorbed onto clay minerals and amorphous oxides under the prevailing geochemical conditions with low pH values. When accounting for anion adsorption in the simulation, Br − concentrations were well predicted, which validated the dispersivity parameterization.